Word and Nonword Repetition Abilities in Spanish Language: Longitudinal Evidence from Typically Developing and Late Talking Children. (4th December 2017) - Rujas, Irene; Mariscal, Sonia; Casla, Marta; Lázaro, Miguel; Murillo, Eva
Abstract: This longitudinal study examined the early word and nonword repetition abilities of monolingual Spanish speaking children. We explored the role that word status, word length, and time play in repetition performance of children with different vocabulary levels. We also examined the predictive value of vocabulary level in repetition abilities. Thirty-seven children participated in this study: 15 late talkers and 22 typically developing children. Families completed the Spanish version of the MacArthur Communicative Developmental Inventory (MCDI) at age 2; children performed a word and nonword repetition task at three different moments, with a temporal interval of 6 months between Time 1 and Time 2, and eight months between Time 2 and Time 3, periods during which linguistic development takes place. We found significant effects for word status, word length, vocabulary level and time: words are repeated better than nonwords; one syllable items are easier to repeat than two and three syllable ones; the performance of late talking children is lower compared to typically developing children throughout the study; and repetition abilities improve longitudinally. In addition, early vocabulary level predicts subsequent repetition abilities and early nonword repetition abilities predict future nonword repetition performance.